Platform technologies and visual analytics for inertial sensors - Leadbetter, R.; James, D. (Journal of Fitness Research, 2016)
A software package for control and visualisation of an inertial sensor system was developed. This was achieved using the software environment MATLAB. Through a number of iterative development stages, the system grew into a flexible, user-friendly platform. Future developments are expanding the system into the cloud.